2020
DOI: 10.17533/udea.redin.20200474
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of airfoil with wavy leading edge at high Reynolds number regime

Abstract: In this work, a numerical study of flow around an airfoil with wavy leading edge is presented at a Reynolds number of 3X106. The flow is resolved by considering the RANS (Reynolds Average Navier-Stokes)equations. The baseline geometry is based on the NACA 0021 profile. The wavy leading edge has an amplitude of 3% and wavelength of 11%, both with respect to the airfoil chord. Cases without and with wavy leadingedges are simulated and compared. Initially, studies of the numerical sensitivity with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Based on the profile of the NACA 0021 airfoil with wavy leading edge modification, Fonseca et al studied the flow around the airfoil at Reynolds number 3×10 6 numerically. The research results showed that the maximum lift coefficient and the stall angle of the wave leading edge increase and the drag coefficient of the wave leading edge airfoil is higher than that of the straight leading edge airfoil, when the angle of attack is close to the stall angle (Fonseca et al 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Based on the profile of the NACA 0021 airfoil with wavy leading edge modification, Fonseca et al studied the flow around the airfoil at Reynolds number 3×10 6 numerically. The research results showed that the maximum lift coefficient and the stall angle of the wave leading edge increase and the drag coefficient of the wave leading edge airfoil is higher than that of the straight leading edge airfoil, when the angle of attack is close to the stall angle (Fonseca et al 2020).…”
Section: Introductionmentioning
confidence: 96%